One-step construction of bifunctional nanoprobes for NIR afterglow and T2-weighted MR imaging. Issue 12 (15th June 2022) - Zhu, Yaqi; Yang, Jian; Wang, Mingwei; Meng, Yangqi; Jiang, Rongyun; Zhu, Hancheng; Yan, Duanting; Liu, Chunguang; Xu, Changshan; Liu, Yuxue
Abstract: In this study, spinel-phase Zn2 Ga3- x Fe 3+ x Ge0.75 O8 ( x  = 0, 0.002, 0.004, 0.02, 0.04, 0.08, 0.2) and Zn2 Ga2.98- x Fe 3+ x Cr0.02 Ge0.75 O8 ( x  = 0, 0.0004, 0.001, 0.002 0.003, 0.004) nanoparticles were prepared by one-step hydrothermal method in combination with vacuum annealing. For ZGGO: Fe 3+ nanoparticles, the near infrared (NIR) emissions (∼725 nm) originate from the 4 T1 ( 4 G)→ 6 A1 ( 6 S) transition of Fe 3+ occupying octahedral and tetrahedral sites of Ga 3+ . Furthermore, their afterglow time is more than 15 min and Fe 3+ doping will influence the generation of antisite defects pair ( Ga Zn 0 − Zn Ga ′ ). For Cr 3+ and Fe 3+ co-doped ZGGO nanoparticles with average size of ∼46 nm, the NIR persistent luminescence around ∼700 nm, originating from the 2 E→ 4 A2 and 4 T2 → 4 A2 transitions of Cr 3+, can be observed and the afterglow time exceeds 850 min. With the increase of Fe 3+ concentration, the afterglow intensity decreases due to the decreased number of ( Ga Zn 0 − Zn Ga ′ ) defects and deeper traps. In particular, autofluorescence-free imaging and MR imaging were successfully realized by using ZGGO: Cr 3+, Fe 3+ 0.002 nanoparticles dispersed in the simulated biological fluid environments (H2 O, SLS and HSA). Their clear afterglow images can be acquired within 3 min after the stoppage of the UV irradiation and their transversal relaxivity (r2 ) is in the range of 227–140 mM −1 s −1, which is close to the conventional Feridex T2 agent (108 mM −1 s −1 ). Our results suggest that ZGGO: Cr 3+, Fe 3+ nanoprobes have potential applications in the diagnosis and therapy of disease.